V chem sekret fenomenal'nykh mirovykh rekordov kitaiskikh sportsmenok v bege na dlinnye distantsii i staierov-"gortsev"? - Yakimov, A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
About the World records set of chinese long distance runners in the ninetees - which exploded like "bombs" in the running world. The performance development in these distances was very strong over the last years. Author tries to explain this phenomenon.